A secure trust aware ACO-Based WSN routing protocol for IoT - Sharmin, Afsah; Anwar, Farhat; Motakabber, S. M. A.; Hassan Abdalla Hashim, Aisha (ASTES Publishers, 2022)
The Internet of Things (IoT) is the evolving paradigm of interconnectedness of objects with varied architectures and resources to provide ubiquitous and desired services. The popularization of IoT-connected devices facilitating evolution of IoT applications does come with security challenges. The IoT with the integration of wireless sensor networks possess a number of unique characteristics, so the implementation of security in such a restrictive environment is a challenging task. Due to the perception that security is expensive in terms of computation, power and user-interface components, and as sensor nodes or low-power IoT objects have limited resources, it is desired to design security mechanisms especially routing protocols that are light weighted. Bio-inspired mechanisms are shown to be adaptive to environmental variations, robust and scalable, and require less computational and energy resources for designing secure routing algorithms for distributed optimization. In IoT network, the malicious intruders can exploit the routing system of the standardized routing protocol, e.g., RPL (The Routing Protocol for Low-Power and Lossy Networks), that does not observe the node’s routing behavior prior to data forwarding, and can launch various forms of routing attacks. To secure IoT networks from routing attacks, a secure trust aware ACO-based WSN routing protocol for IoT is proposed here that establishes secure routing with trustworthy nodes. The trust evaluation system, is enhanced to evaluate the node trust value, identify sensor node misbehavior, and maximize energy conservation. The performance of the proposed routing algorithm is demonstrated through MATLAB. Based on the proposed system, to find the secure and optimal path while aiming at providing trust in IoT environment, the average energy consumption is minimized by nearly 50% even as the number of nodes has increased, as compared with the conventional ACO algorithm, a current ant-based routing algorithm for IoT-communication, and a present routing protocol RPL for IoT.